EFEK PEMBERIAN EKSTRAK AIR DAUN PLUKENETIA VOLUBILIS (SACHA INCHI) TERHADAP KADAR TRIGLISERIDA PADA MENCIT DIABETES MELLITUS - Dewi Handayani; Zakiyah, Nesfitri Aufa; Amir, Hermansyah (University of Bengkulu, 2025)
This research aims to determine the content of secondary metabolites and the effect of administration and effective dose of water extract of Plukenetia Volubilis (sacha inchi) leaves on triglyceride levels in diabetic mice. The research design is experimental with the pre-post test method and control group design. The samples used were 21 male white mice which were divided into 7 groups, namely the normal group, the positive control group (given glibenclamide), the negative group (only alloxan), and the treatment group (treated with sacha inchi leaf water extract) with different doses that is dosis dosis 0,26 g/kgBB, 0,525 g/kgBB, 0,525 g/kgBB (boiled water), 1,05 g/kgBB. Taking glucose and triglyceride data was checked 3 times within 10 days using a glucometer and lipid pro. The data analysis used the Analysis of Variance (ANOVA) method with the Statistical Package For Social Science (SPSS) Statistic IBM 23. This research began with testing of phytochemical compounds to determine secondary metabolism. Phytochemical test results with aqueous extract of Plukenetia Volubilis leaves contain tannins, alkaloids, saponins, and flavonoids. During 10 days of testing blood glucose and triglyceride levels on mice induced by alloxan, the effective dose was reduced on day 7 with a dose of 4 (1,05 g/kgBB). Based on the results of this research , it can be concluded that Plukenetia Volumbilis (Sacha Inchi) leaf water extract was detected to reduce blood glucose levels in mice and reduce blood triglyceride levels in mice for a certain time. Keywords : Triglycerides, Diabetes, Sacha Inchi, Plukenetia Volumbilis, Aloksan